Adaptation of potentially preventable medication-related hospitalisation indicators for Indigenous populations in Australia using a modified Delphi technique - Amanda J Wheeler; Lisa M Kalisch Ellett; Jean Marie Spinks; Geoffrey Spurling; Theo Theodoros; Daniel Williamson (BMJ Open)
Objectives One of the outcomes of a medication review service is to identify and manage medication-related problems (MRPs). The most serious MRPs may result in hospitalisation, which could be preventable if appropriate processes of care were adopted. The aim of this study was to update and adapt a previously published set of clinical indicators for use in assessing the effectiveness of a medication review service tailored to meet the needs of Indigenous people, who experience some of the worst health outcomes of all Australians.iDesign A modified Delphi technique was used to: (i) identify additional indicators for consideration, (ii) assess whether the original indicators were relevant in the context of Indigenous health and (iii) reach consensus on a final set of indicators. Three rounds of rating were used via an anonymous online survey, with 70% agreement required for indicator inclusion.Setting The indicators were designed for use in Indigenous primary care in Australia.Participants Thirteen panellists participated including medical specialists, general practice doctors, pharmacists and epidemiologists experienced in working with Indigenous patients.Results Panellists rated 101 indicators (45 from the original set and 57 newly identified). Of these, 41 were accepted unchanged, seven were rejected and the remainder were either modified before acceptance or merged with other indicators. A final set of 81 indicators was agreed.Conclusions This study provides a set of clinical indicators to be used as a primary outcome measure for medication review services for Indigenous people in Australia and as a prompt for pharmacists and doctors conducting medication reviews.Trial registration number The trial registration for the Indigenous Medication Review Service feasibility study is ACTRN12618000188235.